National Goals and Scientific Priorities - A. S. Kulagin (Ekonomika Nauki)
The article discusses the impact of the goals chosen by the state for its scientific and technical sphere considering the concept of scientific priorities. The approaches used in the USSR to the formation and implementation of scientific priorities made it possible to solve a number of strategic national economic problems in a short time. The author has investigated modern approaches to the formation and implementation of priority directions for the development of science, as well as assessing the effectiveness of research activities. The analysis showed inadequacy of assessing the activities of scientific organizations on the basis of publication and citation indicators.